NGHIÊN CỨU THÀNH PHẦN HÓA HỌC LÁ CÂY SƠN TRÀ POILANE (ERIOBOTRYA POILANEI J.E. VID.), HỌ HOA HỒNG (ROSACEAE) II. TRITERPEN KHUNG URSAN VÀ OLEAN - Thiện, Đinh Gia; Hoàng Anh, Nguyễn Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Three triterpenes with the ursane and oleane skeleton were isolated from acetylated fraction of Eriobotrya poilanei’s leaves. Their structures were elucidated by analysis of MS, NMR spectra and comparison with the published data as 2α,3β-diacetat-12 oleanen-28-oic acid; 1β,2β,3β-triacetat-19α-hydroxy 12-ursanen-28-oic acid; 1β,3β-diacetat-19α-hydroxy-2-oxo 12-ursanen-28-oic acid.